ПРОТОКОНЦЕПЦІЇ ЕМІГРАЦІЇ В ЄВРОПЕЙСЬКІЙ ФІЛОСОФІЇ ХІХ СТОЛІТТЯ - Цимбал, Т. В. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
У статті представлено досвід осягнення протоконцепцій еміграції у європейській філософії ХІХ ст.. Розглядаються ідеї німецької класичної філософії про межі мобільності як межі демократії і прав людини. Проаналізовано внесок марксизму в розробку проблеми еміграції з позицій соціальної детермінації. Подано оригінальні погляди філософів-волюнтаристів на локальну вкоріненість людини як рівень буденності та духовної бідності. Вивчення провідних філософських поглядів на проблему еміграції до межі ХІХ-ХХ ст. виявило неоднозначність провідних тенденцій, що передують постановці проблеми локального вкорінення людини. Ключові слова: еміграція, буттєвісне вкорінення, локальна вкоріненість, автономність, суверенність. Татьяна Цимбал. Протоконцепции эмиграции в европейской философии ХIХ столетия. В статье представлен опыт осмысления протоконцепций эмиграции в европейской философии ХIХ ст.. Рассмотрены идеи немецкой классической философии о границах мобильности как границах демократии и прав человека. Проанализирован вклад марксизма в разработку проблемы эмиграции с позиций социальной детерминации. Представлены оригинальные взгляды философов- волюнтаристов на локальную укорененность как уровень повседневности и духовной бедности. Изучение основных философских взглядов на проблему эмиграции до рубежа ХIХ-ХХ ст. выявило неоднозначность ведущих тенденций, которые предшествуют постановке проблемы локального укоренения человека. Ключевые слова: эмиграция, бытийное укоренение, локальная укорененность, автономность, суверенность. Tatyana Tsymbal. Protokontsepts of emigration in European philosophy of the nineteenth century. The article presents the experience of understanding protokonseption of emigration in the European philosophy of the nineteenth century in context of the author’s theory of human being-rootedness. Considered the idea of classical German philosophy of the limits of mobility as the borders of democracy and human rights, the right to «visit» and opposed it right «hospitality». The contribution of Marksism to the development of emigration problems from the standpoint of the social determination. Presents original views philosopher’s voluntarisms to the local rootedness as the level of everyday life, spiritual poverty, and on the contrary, a person’s life as a wandering on the manifestation of freedom and spiritual wealth. Learning the basic philosophical views on the problem of emigration and existential rootedness until the turn of the nineteenth and twentieth centuries has revealed the ambiguity and inconsistency of the leading trends that predate the formulation of the problem of local people rooting justification conditions, the determinant, and the ways and means of self-realization of the individual. Search the metaphysical unity of views on human existence as the interaction of the objective and the subjective,